Early recurrence detected by (18)F-FDG PET/CT in patients with resected pancreatic ductal adenocarcinoma - Wang, Li (Medicine (Baltimore), 2020)
(18)F-fluoro-2-deoxy-D-glucose positron emission tomography integrated with computed tomography ((18)F-FDG PET/CT) has been proved to be practical in detecting occult malignant lesions. However, the evidence of its utility in detecting early recurrence after resection of pancreatic ductal adenocarcinoma (PDAC) is lacking. Therefore, the primary aim of the present study is to evaluate the diagnostic value of (18)F-FDG PET/CT in the early postoperative period after radical resection of PDAC. This retrospective study included 32 patients who had (18)F-FDG PET/CT scan within 6 months after radical resection of PDAC between January 2010 and December 2018. In total, 10 positive PET results were found at surgical margins of remnant pancreas, 12 at locoregional lymph nodes, 5 at distant areas, with the corresponding mean maximum standard uptake value (SUV(max)) of 5.8 ± 1.1, 5.9 ± 0.9, and 6.4 ± 0.7, respectively. The median follow-up time was 23.5 months (range: 8–75 months), and the median survival time was 39.5 months (95% confidence interval: 14.6–64.4 months) for the entire cohort. Patients with positive PET findings at either locoregional lymph nodes or distant areas obtained significantly poorer overall survival (OS) than those without increased FDG uptake at the corresponding areas (P = .003 and P < .001, respectively). Whereas comparisons of OS between patients with or without increased FDG uptake at the surgical margin of remnant pancreas presented no statistically difference (P = .742). The early application of (18)F-FDG PET/CT after radical resection of PDAC could stratify the prognosis of patients well by detecting occult early recurrence at locoregional lymph nodes and distant areas efficiently.